GE_GERICHTE P/7090/2011 vom 27. September 2012 - GE Cour de justice (2012)
; DÉFENSE D'OFFICE ; INDEMNITÉ(EN GÉNÉRAL) ; TAXE SUR LA VALEUR AJOUTÉE ; DOMICILE À L'ÉTRANGER | CPP.135; RAJ.16; LTVA.1; LTVA.6; LTVA.18; LTVA.27; LTVA.3; CO.112